Upaya Guru dalam Menanamkan Sikap Sosial Peserta Didik Kelas VI melalui Pembelajaran Tema 2 (Persatuan dalam Perbedaan) - Hendro Febbrian; Nurul Febrianti (Departement of Mathematics Education, 2023)
The importance of instilling social attitudes among elementary school students has attracted the attention of researchers. Due to things that deviate from the social attitudes of the participants, such as there are students who come late to school, there are students who throw garbage carelessly, students do not do class pickets, students do not do homework, students cheat when doing school assignments, there are students students who are embarrassed to ask and there are students who are embarrassed to answer questions. This research aims to find out the teacher's efforts in instilling social attitudes in class VI students through learning the second theme, especially Social Studies and Civics lessons. This research was conducted at SD Negeri Cengkareng Timur 01 Pagi. The type of research used is qualitative using descriptive methods. The research subjects consisted of students, class VI teachers, and school principals. Researchers collect data by interviews, observation, and documentation. Interviews were conducted with class VI teachers and school principals. Observations were made to all students, informants by observing learning activities carried out at school. The results showed that not all of the students had good social attitudes. The teacher's efforts in instilling social attitudes in class VI students can be adjusted to the needs of students' social attitudes. There are eight social attitudes of students, namely (1) honest attitude, (2) discipline attitude, (3) responsibility attitude, (4) caring attitude towards the environment, (5) tolerance attitude, (6) mutual cooperation attitude, ( 7) polite attitude, and (8) confident attitude.